Niveles de sobrecarga y ansiedad en cuidadores primarios de personas con discapacidad intelectual del Hospital Básico Macará Periodo 2021 - Merchán Cumbicus, Vanessa Lizeth (2022)
In recent years, the caregiver overload in disability has been one of the least studied problems in the primary health care, which is a public health problem given the implications, it has on the quality of life of those who suffer from it. For this reason, the principal objective of this studio was to establish the relationship between levels of overload and anxiety levels in primary caregivers of people with intellectual disabilities at the Macará Basic Hospital. For the present research, a cross-sectional, prospective, descriptive-correlational methodology was used. The sample consisted of 40 primary caregivers of patients with intellectual disabilities to whom the Zarit Caregiver Overload Scale and the Hamilton Anxiety Scale were applied. The results of the study indicate the presence of overload is evident in more than half of the study population, with the highest levels of intense overload and light overload. Also, more than half of the caregivers present anxiety, with a predominance of moderate/severe and mild anxiety levels. Finally, a statistically significant correlation was found between the variables overload and anxiety, with the higher the level of overload, the greater the presence of anxiety